Implementation of Accounting Code of Ethics Based on Islamic and Christian Scriptures for Accounting Students at Medan State University - Lubis, Anggi Zahwa Yunita; Sihombing, Andico Julius; Pasaribu, Benediktus Hasoloan; Nasirwan, Nasirwan (Economic: Journal Economic and Business, 2024)
The code of ethics of accountants cannot be separated from the moral and spiritual values that originate from the teachings of the world's major religions. This study seeks to explore how the perspective of religious scriptures can provide an ethical foundation for the accounting profession. By examining the ethical principles contained in the Qur'an, Psalms, Torah, and Gospel, it is hoped that a more comprehensive understanding of the code of ethics of accountants can be obtained that is in line with spiritual and humanitarian values. This research will be conducted in September. The place of research in this study is at the State University of Medan. The type of data used in this study is subject data. The data sources in this study use primary and secondary data. Data collection techniques used in this study are observation, interviews and documentation. The stages of data analysis in this study start from data reduction, then data presentation and final conclusions.